The 4 Quadrants of Administrative Effectiveness - Rob Jenkins (Academic Chairpersons Conference Proceedings, 2018)
Mr. Jenkins will introduce attendees to a new paradigm for thinking about administrative effectiveness, charting tasks and problems on the axes of responsibility and control – what you responsible for, and how much control you have over it. The best administrators push themselves into the “high responsibility-low control quadrant. This workshop will also include practice using a unique assessment tool that allows administrators to chart themselves using this system, and see in which quadrant they typically inhabit.
Keywords: Effective Administration Responsibility Quadrant System